Social Businesses with An Export Profile as a Mechanism to Promote Entrepreneurship and Improve Welfare (European Journal of Marketing and Economics, 2026)
The increase in unemployment rates at the international level, as a consequence of the deep financial crisis of the beginning of the 21st century, has caused the labor market to become increasingly restricted, complicating the insertion of a population of productive age. In addition, the lack of employment has exacerbated a series of social problems, including poverty, insecurity, undernourishment, among others, in a large part of Latin America. Therefore, the impulse of social enterprises can contribute to the creation of jobs and combat this problem, generating wellbeing not only within a region but also in others with similar situations, generating an area of ​​opportunity for those social enterprises with an export profile. Based on the above, this paper begins with a documentary research process of specialized literature on social business and later analyzes a group of students' perception on the impact that this model can produce, as well as the limitations for its implementation, through an exploratory and descriptive study, guided by the qualitative approach since a questionnaire of open questions about these topics was used as a research instrument. The answers were analyzed in such a way that similarities and differences could be detected among students' perception. Results shown that the main benefits are the creation of direct jobs in the country of origin and indirect in other markets as well as the emergence of productive chains while among the constraints include ignorance of the export logistics process and tariff rates. Finally, a series of recommendations are proposed in order to strengthen the dissemination of this business model.
Keywords: social business, entrepreneurial culture, entrepreneurial teams.